Carer and clinician perceptions of the use of emergency medical services by people with dementia: a qualitative study. (2019) - Voss, Sarah; Brandling, Janet; Black, Sarah; Cheston, Rik; Cullum, Sarah; Iliffe, Steve; Purdy, Sarah; Benger, Jonathan
Abstract: A growing number of older people are accessing emergency medical services (EMS), and many calls to EMS are made by, or on behalf of, people with dementia. Their needs are frequently complex; however, EMS staff are often given minimal guidance on ensuring patient safety, accurate diagnosis, and timely transfer to the most appropriate care. This study aimed to qualitatively explore the EMS experiences of carers for people with dementia and assess the views of EMS staff on the management of dementia, using focus groups and interviews. Themes were focussed on the circumstances surrounding EMS calls to people with dementia. These can prove frustrating due to a lack of information sharing, limited alternatives to hospital attendance and the amount of time that it can take to meet the complex needs of a person with dementia.